Perceived stress by mototaxi drivers and its relationship with sociodemographic and occupational characteristics - Lídia Cíntia Silva Cidreira; Jules Ramon Brito Teixeira; Fernanda Carneiro Mussi (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To investigate the association of sociodemographic and occupational characteristics with a high level of perceived stress in motorcycle taxi drivers. Method: Cross-sectional study carried out with motorcycle taxi drivers who answered instruments on sociodemographic and occupational variables - Perceived Stress Scale, Job Content Questionnaire and Effort-Reward Imbalance. Descriptive statistics, Pearson's chi-square test and Poisson regression with robust variance were used. Statistical significance was 5%. Results: Of the 800 motorcycle taxi drivers, 46.8% had a high level of perceived stress. In the multivariate analysis, a high level of stress was associated with low control over work (PR=7.76; 95%CI=5.19-11.61), low social support at work (PR=3.87; 95%CI =2.95 5.08), working hours longer than eight hours a day (RP=1.47; 95%CI=1.21-1.78) and monthly income less than or equal to two minimum wages (PR=1.34;95%CI=1.13-2.58). Conclusion: Long working hours, occupational stressors and low income were associated with a high level of perceived stress. Public policies and interventions to minimize occupational stressors are essential.